Radioactivity and Exposure to Radiation in Lithium Mining in Western Australia - Gbondo, David; Pham, Minh; Zhao, Yun; Rumchev, Krassi (ScienceDirect, 2025)
Background Lithium is a crucial commodity; however, the mining and processing of lithium is associated with exposure to Naturally Occurring Radioactive Material (NORM) from the uranium-238 and thorium-232 decay chains. The sources and pathways of exposure include the inhalation of dust containing alpha-emitting radioactive elements, radon, thoron and their decay products, the ingestion of drinking water containing alpha and beta emitting radioactive elements, and exposure to gamma. Methods This study used industry radiation emission and occupational exposure to NORM data from three surface lithium mines in Western Australia (WA) for the period between 2018 and 2024. Samples were collected from the lithium ore, spodumene concentrate, tantalum concentrate, wet tailings and dry tailings to determine radioactivity. Exposure to radiation was compared between the departments including Administration and Support Services, Mining, Crushing & Processing, and Maintenance. Results The study found a high mean radiation emission in the tantalum concentrate of 2.169 Bq/g. The radiation exposures for all the departments ranged from 0.262 mSv per year to 0.544 mSv year, which were significantly below the occupational dose limit of 20 mSv per year. The study found that the reverse osmosis plants significantly reduced the radiation levels in the bore water after treatment. Conclusion The study demonstrated low levels of radiation exposure with the treatment of bore water using reverse osmosis plants. Based on the study results, proactive control measures to protect workers from exposure to tantalum concentrate and the treatment of bore water should be considered.